P465 UC trial designed more than 5 years ago in the light of the EMA guideline on the development of new medicinal products for the treatment of ulcerative colitis. (25th January 2019) - Laoun, R; Hofmann, R
Abstract: Background: Developing a new drug in ulcerative colitis (UC) is challenging. More challenging is the clinical trial design. We highlight, here, the Phase 3 trial design of a new 5ASA drug (TP0503) and compare it to the current EMA 'guideline on the development of new medicinal products for the treatment of ulcerative colitis'. Methods: Each item in the EMA guideline was compared with the TP0503 protocol (Asacol 1600 mg vs. Asacol 400 mg) and GEMINI1 trial (vedolizumab). This comparison will cover the patient selection (section 4), efficacy assessment (section 5), study design (section 6). Safety aspects (section 7) and the risk management plan (section 8) were well-respected by both trials. Results: As per the EMA guideline, patient selection in TP0503 and GEMINI1 was based on symptoms, endoscopic and histological findings. Patients with malignancy and Clostridium D. infection were excluded. TP0503 was also in line with the Jairath et al. recommendation concerning the endoscopic severity of disease at entry. All TP0503 patients had a Mayo Endoscopic Score (MES) ≥2. MES was assessed by one central reader. This is one of the first trials that used central reading for inclusion and efficacy assessments. In the efficacy assessment, TP0503 respected each item of the guideline looking at the symptomatic and endoscopic remission as a treatment goal for induction and maintenance of remission in UC. In TP0503, the primary endpoint was a co-primary endpoint at Week 8 of clinical remission and endoscopic remission as defined by MAYO ≤2 without any subscore >1, whilst GEMINI trial used the total MAYO response. Remission was only secondary endpoint, not in line with EMA guideline. For the study design, TP0503 respected each item of the guideline except for two. For ethical reasons, it was not possible to randomise UC patients to a placebo arm therefore TP0503 trial was a non-inferiority trial. Nor where they stratified according to prior treatment. With regards to missing data, TP0503 considered all missing data as failures, unlike the GEMINI trial where the LOCF was used to manage some missing data. Patients on topical co-medication were excluded from both trials. Looking at safety aspects, beside the exclusion of acute severe colitis and patients with pouchitis, which are not part of the mesalazine indications, TP0503 respected all other criteria. Conclusions: TP0503 trial was designed to insure the most objective evaluation of efficacy in UC patients. The most stringent criteria were used to include and assess patients with mild and moderate UC patients.